Aging-resistant flame-retardant energy storage charging cable and preparation method thereof
By adopting a multi-layer structure in the cable and using the flame retardant powder and efficient aging-resistant additives synthesized by the electrostatic self-assembly method, the problem of poor flame retardant and aging resistance performance of the cable is solved, and higher cable performance and safety are achieved.
Patent Information
- Application Number
- CN202411471482.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-22
AI Technical Summary
In the prior art, the flame retardant and aging resistance of cables are poor.
Using a structure of conductive wire core, winding lining layer, armor layer, flame retardant layer and aging-resistant layer arranged in sequence from the inside to the outside, a white powder with flame retardant effect is synthesized by electrostatic self-assembly method, and doped into polyethylene as a flame retardant layer material, to synthesize an aging-resistant additive with high efficiency light stability and ultraviolet absorption ability, and add it to polystyrene as an aging-resistant layer material.
It significantly improves the flame retardant effect, aging resistance and mechanical properties of the cable, extends the service life of the cable and enhances its safety performance.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of charging cables, and in particular relates to an aging-resistant, flame-retardant, energy-storage charging cable and a preparation method thereof. Background Art
[0002] With the rapid development of fields such as energy storage and electric vehicles, energy storage charging cables are being used more and more widely, and the requirements for the aging resistance and flame retardant properties of cables are becoming higher and higher. In order to improve the service life and safety of cables, the innovation of cable materials and preparation methods has become the focus of research. At the same time, with the increasing awareness of environmental protection, higher requirements are also put forward for the environmental performance of cable materials. Therefore, the research and development of aging-resistant and flame-retardant energy storage charging cables has important practical significance and market demand.
[0003] The Chinese invention patent application with publication number CN 112980102 A discloses a charging pile cable material and a preparation method thereof, wherein the charging pile cable material is composed of 55-70 parts of EPDM rubber, 10-20 parts of ethylene octene copolymer resin, 8-12 parts of compatibilizer, 6-12 parts of polyethylene-acrylate rubber, 5-10 parts of ethylene-vinyl acetate copolymer, 2-5 parts of polyphenylene ether, 60-80 parts of flame retardant, 20-30 parts of flame retardant synergist, 15-25 parts of thermal conductive filler, 0.5-1 parts of polyethylene wax, 1.2-2 parts of antioxidant, 0.9-1.2 parts of cross-linking agent, and 0.1-0.3 parts of anti-degradant. The prepared charging pile cable material has excellent softness, low thermal resistance, crack resistance, and high insulation, but its flame retardant performance and aging resistance still have room for improvement. Summary of the invention
[0004] The object of the present invention is to provide an aging-resistant flame-retardant energy storage charging cable and a preparation method thereof, so as to solve the technical problem that the flame retardant performance and aging resistance performance of the cable in the prior art are poor.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides an aging-resistant and flame-retardant energy storage charging cable, comprising a conductive core, a wrapped inner lining layer, an armor layer, a flame-retardant layer and an aging-resistant layer arranged in sequence from the inside to the outside, wherein seven conductive cores are arranged, which are tightly combined with one in the middle and six on the outer layer, the conductive core comprises an internal conductive core conductor and an external insulating layer, the seven conductive cores are twisted and connected to each other and are wrapped with a wrapped inner lining layer on the outside, a layer of armor layer is wrapped on the outside of the wrapped inner lining layer, a layer of flame-retardant layer is wrapped on the outside of the armor layer, and a layer of aging-resistant layer is wrapped on the outside of the flame-retardant layer.
[0007] Preferably, the method for preparing the flame retardant layer material comprises the following steps:
[0008] Q1: Toluene, polymethylhydrogensiloxane and chloroplatinic acid are added to a three-necked flask equipped with a reflux condenser and a magnetic stirrer, wherein chloroplatinic acid is dissolved with isopropanol, heated under a nitrogen atmosphere, and then methyl methacrylate is slowly added dropwise, followed by a heating reaction, and after the reaction is completed, vacuum distillation is performed, washed with ethanol, and centrifuged to obtain product 1, product 1 and sodium hydroxide solution are added to a flask equipped with a fractionation device, heated for hydrolysis, methanol is fractionated to obtain a reaction solution, a dilute hydrochloric acid solution is added dropwise to the reaction solution to adjust the pH, a precipitate is obtained, washed, and dried to obtain carboxylated silicon;
[0009] Q2: Dissolve chitosan in acetic acid solution to obtain chitosan solution, and evenly disperse ammonium polyphosphate in deionized water, then add the chitosan solution dropwise, stir, centrifuge, obtain a precipitate, wash, and obtain product 2, evenly disperse product 2 in deionized water to obtain a suspension, then dissolve carboxylated silicon in dilute ammonia water, adjust the pH and add to the suspension, stir, wash, centrifuge, and obtain product 3, and vacuum dry product 3 to obtain a white powder;
[0010] Q3: The polyethylene and white powder are vacuum dried, heated to melt and blended, and then hot-pressed to obtain the flame retardant layer material.
[0011] In the above process, the synthesis process of carboxylated silicon is as follows:
[0012]
[0013] White powder with flame retardant effect was synthesized in water by electrostatic self-assembly method. Ammonium polyphosphate and chitosan were used as acid source and carbon source of the flame retardant system respectively. Carboxylated silicon was coated on the surface of ammonium polyphosphate and chitosan. Carboxylated silicon easily migrated and concentrated on the surface of polyethylene material during combustion, and could form a protective silicon-carbon layer at high temperature. Carboxylated silicon has high ductility, softness and good hydrophobicity, which can improve the toughness of polyethylene material.
[0014] Preferably, the mass ratio of toluene, polymethylhydrogensiloxane, chloroplatinic acid and methyl methacrylate in Q1 is (39.8-40.1): (19.9-21.1): (0.002-0.003): (29-31), the dosage ratio of chloroplatinic acid to isopropanol is (4.5-6.1) g: 1L, heated to 80-90°C, the dropwise addition time is 1-2h, the heating reaction temperature is 140-150°C, the heating time is 30-34h, the volume fraction of the sodium hydroxide solution is 10vt%, the heating hydrolysis temperature is 100-120°C, the time is 2-3h, the pH is adjusted to 6, the drying temperature is 60-70°C, and the time is 10-12h.
[0015] Preferably, the deacetylation degree of chitosan in Q2 is 95%, the polymerization degree of ammonium polyphosphate is greater than 1000, the mass ratio of chitosan, ammonium polyphosphate and carboxylated silicon is (0.8-1.1):(10-10.2):(0.9-1.1), the stirring time is 3-5 min, the centrifugal speed is 3000-4000 rpm, the centrifugal time is 8-10 min, the pH is adjusted to 8, the vacuum drying temperature is 60-70°C, and the time is 10-12 h.
[0016] Preferably, the heating melting temperature in Q3 is 150-170°C, the blending time is 8-10min, the rotation speed is 60-80rpm, and the hot pressing process is: first preheating at 2MPa and 180°C for 5min, then pressurizing to 30MPa, maintaining at 180°C for 3min, and then compressing at room temperature and 30MPa for 3min.
[0017] Preferably, the method for preparing the anti-aging layer material comprises the following steps:
[0018] S1: Dissolve cyanuric chloride in toluene, slowly add N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine in an ice-water bath, add sodium hydroxide aqueous solution after the reaction, heat to react, extract with water and ethyl acetate after the reaction, separate and combine the organic phases, dry, rotary evaporate, and vacuum dry to obtain intermediate 1;
[0019] S2: In an ice-water bath, add intermediate 1, chlorobenzene and anhydrous aluminum chloride into a three-necked flask equipped with a mechanical stirrer and stir. After stirring, add hydroquinone into the three-necked flask and heat to react. After the reaction, slowly drop dilute hydrochloric acid into the three-necked flask, distill at normal pressure, heat, filter while hot, wash, and dry to obtain intermediate 2;
[0020] S3: Add N,N-dimethylformamide and sodium hydroxide into a three-necked flask, heat and stir, then add intermediate 2, increase the temperature, dropwise add a mixed solution of 1-chlorohexane and N,N-dimethylformamide, continue the reaction at a constant temperature, cool, filter, wash, dry, and recrystallize to obtain an anti-aging additive;
[0021] S4: drying the polystyrene and the anti-aging additive, melt-blending them, and hot-pressing them to obtain an anti-aging layer material.
[0022] In the above process, cyanuric chloride and N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine are used as starting materials, and intermediate 1 is obtained after substitution, and then a substitution reaction is carried out with hydroquinone to construct an intramolecular hydrogen bond, and then the hydroxyl group in the structure is etherified by chlorohexane to obtain an anti-aging additive. The structure contains a piperidinamine group and an intramolecular hydrogen bond, which makes it have high-efficiency light stability and ultraviolet absorption functions. The synthesis process of the anti-aging additive is as follows:
[0023]
[0024] Mass spectrometry analysis showed m / z: 693.57 (100.0%), 694.57 (45.2%), 695.57 (11.2%), 694.56 (2.6%), 696.58 (1.4%).
[0025] Preferably, the mass ratio of cyanuric chloride to N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine in S1 is (18-18.88):(42.12-42.5), the heating temperature is 70-80°C, the reaction time is 12-16h, and the number of extractions is 3-5 times.
[0026] Preferably, in S2, the dosage ratio of intermediate 1, chlorobenzene, anhydrous aluminum chloride and hydroquinone is (1.5-1.7) g: (10-14) mL: (0.4-0.5) g: (0.3-0.4) g, the stirring time is 30-40 min, the heating temperature is 80-90°C, the heating time is 4-5 h, the volume fraction of dilute hydrochloric acid is 2vt%, and the heating temperature is 100-120°C.
[0027] Preferably, in S3, the dosage ratio of N,N-dimethylformamide, sodium hydroxide, intermediate 2 and mixed solution is 10 mL: (0.07-0.08) g: (0.9-1.1) g: (0.88-0.9) mL, the heating temperature is 40-50°C, the stirring time is 20-30 min, the heating temperature is 80-90°C, the dropping time is 2-3 min, and the continued reaction time is 6-7 h; in S4, the melting temperature is 220-240°C, and the blending time is 10-15 min.
[0028] Preferably, the method for preparing the aging-resistant flame-retardant energy storage charging cable comprises the following steps:
[0029] Step 1: Twist 40-50 tinned soft copper wires into one strand, arrange and twist them according to one strand in the center and eight strands on the outer layer, and press them tightly to obtain a conductive core conductor. Wrap natural rubber around the outside of the conductive core conductor and combine them tightly to obtain a conductive core.
[0030] Step 2: Arrange the conductive wire cores with one in the center and six on the outer layer, wrap them with a winding lining layer, wrap a layer of armor layer on the outside of the winding lining layer, then wrap a layer of flame retardant layer material on the outside of the armor layer, and wrap a layer of aging-resistant layer material on the outside of the flame retardant layer. After tightly combining, an aging-resistant flame-retardant energy storage charging cable is obtained.
[0031] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0032] 1. The present invention first prepares a white powder with a flame retardant effect, and dopes the white powder into polyethylene to obtain a flame retardant layer material. Chitosan and ammonium polyphosphate are used as carbon sources and acid sources of the flame retardant system to inhibit the combustion of flames. The added carboxylated silicon can form a silicon-containing carbon layer under high temperature conditions to prevent the spread of flames. Subsequently, an anti-aging additive with high-efficiency light stability and ultraviolet absorption capacity is prepared, and the anti-aging additive is added into polystyrene to obtain an anti-aging layer material. The prepared material is used to coat an energy storage charging cable, which can improve the flame retardant effect, aging resistance and mechanical properties of the cable, and increase its service life and safety performance.
[0033] 2. The present invention synthesizes white powder with flame retardant effect through electrostatic self-assembly method. Chitosan, as the carbon source of the flame retardant system, can be thermally decomposed under high temperature conditions to form a carbonized material of a certain thickness on the surface. The presence of these carbonized materials can block the entry of oxygen and has flame retardant properties. The amino and hydroxyl functional groups in chitosan have flame retardant activity and can effectively alleviate the combustion process by absorbing free radicals, etc., to form a stable carbon layer and prevent the spread of flames. Ammonium polyphosphate, as the acid source of the flame retardant system, can produce amine gas through thermal decomposition, increase the inertness of the material and reduce the generation of combustible gases, thereby achieving the purpose of flame retardancy. At the same time, the added carboxylated silicon will quickly gasify under high temperature conditions to produce non-combustible gas, dilute the combustible gas, reduce the oxygen concentration in the combustion zone, and inhibit the combustion of the flame. The white powder is mixed in polyethylene as a flame retardant layer material to effectively improve the flame retardant properties of the cable.
[0034] 3. The piperidine amine group and intramolecular hydrogen bond contained in the anti-aging auxiliary agent synthesized by the present invention can make it have efficient photostability and ultraviolet absorption function. The piperidine amine group has a high electron donor ability and can absorb light energy under the action of ultraviolet light and convert it into stable chemical energy. This conversion can reduce the destructive effect of light energy on the substance and improve the photostability of the substance; the formation of intramolecular hydrogen bonds can stabilize the structure of the substance, making it less likely to be photodegraded when subjected to ultraviolet light. At the same time, hydrogen bonds can also reduce the energy state of the substance, making it less energy to absorb ultraviolet light and reducing the absorption of ultraviolet light. Adding the anti-aging auxiliary agent to polystyrene materials that are easily oxidized and degraded under ultraviolet light can greatly increase the material's anti-aging ability, thereby increasing the service life of the cable. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 It is a cross-sectional schematic diagram of the aging-resistant flame-retardant energy storage charging cable prepared by the present invention.
[0037] Description of the drawings: 1-1. Conductive core conductor; 1-2. Insulation layer; 1. Conductive core; 2. Wrapped lining layer; 3. Armor layer; 4. Flame retardant layer; 5. Anti-aging layer. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The following embodiments of the present invention are used:
[0040] Toluene was purchased from Maoming Xiongda Chemical Co., Ltd., CAS No.: 108-88-3;
[0041] Polymethyl hydrogen siloxane was purchased from Wuhan Xingzhongcheng Technology Co., Ltd., CAS number: 63148-57-2;
[0042] Chloroplatinic acid was purchased from Qianyan Chemical Technology (Wuhan) Co., Ltd., CAS number: 18497-13-7;
[0043] Isopropyl alcohol was purchased from Shandong Mantanghong New Materials Co., Ltd., CAS No.: 67-63-0;
[0044] Methyl methacrylate was purchased from Shandong Jinyueyuan New Materials Co., Ltd., CAS No.: 80-62-6;
[0045] Ethanol was purchased from Shandong West Asia Chemical Co., Ltd., CAS No.: 64-17-5;
[0046] Sodium hydroxide was purchased from Shandong Xinhe New Materials Co., Ltd., CAS No.: 1310-73-2;
[0047] Hydrochloric acid was purchased from Nanjing Shengqinghe Chemical Co., Ltd., CAS No.: 7647-01-0;
[0048] Chitosan was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., CAS number: 9012-76-4;
[0049] Acetic acid was purchased from Jinan Century Tongda Chemical Co., Ltd., CAS No.: 64-19-7;
[0050] Ammonium polyphosphate was purchased from Guangzhou Haoyu International Trade Co., Ltd., CAS number: 68333-79-9;
[0051] Ammonia was purchased from Shandong Mantanghong New Materials Co., Ltd., CAS number: 1336-21-6;
[0052] Polyethylene was purchased from Hefei Tianjian Chemical Co., Ltd., CAS No.: 9002-88-4;
[0053] Cyanuric chloride was purchased from Anhui Youya Chemical Co., Ltd., CAS No.: 108-77-0;
[0054] N-butyl-2,2,6,6-tetramethyl-4-piperidinamine was purchased from Jiangsu Suqian Liansheng Technology Co., Ltd.;
[0055] Ethyl acetate was purchased from Shandong Zhenkun New Materials Co., Ltd., CAS No.: 141-78-6;
[0056] Chlorobenzene was purchased from Shandong Jinyueyuan New Materials Co., Ltd., CAS No.: 108-90-7;
[0057] Anhydrous aluminum chloride was purchased from Shandong Xiya Chemical Co., Ltd., CAS No.: 7446-70-0;
[0058] Hydroquinone was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., CAS number: 123-31-9;
[0059] N,N-dimethylformamide was purchased from Jinan Century Tongda Chemical Co., Ltd., CAS No.: 68-12-2;
[0060] 1-Chlorohexane was purchased from Zouping Mingxing Chemical Co., Ltd., CAS No.: 544-10-5;
[0061] Polystyrene was purchased from Qianyan Chemical Technology (Wuhan) Co., Ltd., CAS number: 9003-53-6;
[0062] Tinned soft copper wire was purchased from Dongguan Jiahao Hardware Electronics Co., Ltd.
[0063] Natural rubber was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., CAS number: 9006-04-6. Example 1
[0064] See also Figure 1As shown, the aging-resistant flame-retardant energy storage charging cable includes a conductive core 1, a wrapped lining layer 2, an armor layer 3, a flame-retardant layer 4 and an aging-resistant layer 5 arranged in sequence from the inside to the outside. The conductive cores are provided with seven, which are tightly combined with one in the middle and six on the outer layer. The conductive core includes an internal conductive core conductor 1-1 and an external insulating layer 1-2. The seven conductive cores are twisted and connected to each other and are wrapped with a wrapped lining layer on the outside. A layer of armor is wrapped on the outside of the wrapped lining layer, a layer of flame-retardant layer is wrapped on the outside of the armor layer, and a layer of aging-resistant layer is wrapped on the outside of the flame-retardant layer. Example 2
[0065] This embodiment discloses a method for preparing a flame retardant layer material, comprising the following steps:
[0066] Q1: 40.05g toluene, 19.95g polymethylhydrogensiloxane and 0.025g chloroplatinic acid were added to a three-necked flask equipped with a reflux condenser and a magnetic stirrer, wherein 5.5g chloroplatinic acid was dissolved with 1L isopropanol, heated to 80°C under a nitrogen atmosphere, and then 30g methyl methacrylate was slowly added dropwise for 1.5h, and then heated to react at 140°C for 32h. After the reaction, it was distilled under reduced pressure, washed with ethanol, and centrifuged to obtain product 1. Product 1 and a sodium hydroxide solution with a volume fraction of 10vt% were added to a flask equipped with a fractionation device, heated to 120°C for hydrolysis for 2h, methanol was fractionated to obtain a reaction solution, a dilute hydrochloric acid solution was added dropwise to the reaction solution to adjust the pH to 6, a precipitate was obtained, washed, and dried at 70°C for 10h to obtain carboxylated silicon;
[0067] Q2: 0.9 g of chitosan with a deacetylation degree of 95% was dissolved in an acetic acid solution to obtain a chitosan solution, and 10.1 g of ammonium polyphosphate with a degree of polymerization greater than 1000 was uniformly dispersed in deionized water, and then the chitosan solution was added dropwise, stirred for 5 min, and centrifuged at 4000 rpm for 8 min to obtain a precipitate, which was washed to obtain product II, and product II was uniformly dispersed in deionized water to obtain a suspension, and then 1.0 g of carboxylated silicon was dissolved in dilute ammonia water, and the pH was adjusted to 8 and then added to the suspension, stirred, washed, and centrifuged to obtain product III, and product III was vacuum dried at 60°C for 12 h to obtain a white powder;
[0068] Q3: After the polyethylene and white powder were vacuum dried, they were melt-blended at 170°C for 10 min at a rotation speed of 70 rpm, preheated at 2 MPa and 180°C for 5 min, then pressurized to 30 MPa, maintained at 180°C for 3 min, and then compressed at room temperature and 30 MPa for 3 min to obtain the flame retardant layer material.
[0069] This embodiment discloses a method for preparing an anti-aging layer material, comprising the following steps:
[0070] S1: 18.44 g of cyanuric chloride was dissolved in toluene, and 42.3 g of N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine was slowly added under an ice-water bath. After the reaction, an aqueous sodium hydroxide solution was added, and the mixture was heated at 70°C for 14 h. After the reaction, the mixture was extracted with water and ethyl acetate for 3 times, and the organic phases were separated and combined, dried, rotary evaporated, and vacuum dried to obtain intermediate 1;
[0071] S2: In an ice-water bath, add 1.6 g of intermediate 1, 12 mL of chlorobenzene and 0.45 g of anhydrous aluminum trichloride to a three-necked flask equipped with a mechanical stirrer and stir for 30 min. After stirring, add 0.35 g of hydroquinone to the three-necked flask, heat at 90°C for reaction for 5 h. After the reaction, slowly drop 2% by volume of dilute hydrochloric acid into the three-necked flask, distill at normal pressure, heat to 110°C, filter while hot, wash, and dry to obtain intermediate 2.
[0072] S3: 10 mL of N,N-dimethylformamide and 0.075 g of sodium hydroxide were added to a three-necked flask, heated at 50°C with stirring for 30 min, then 1.0 g of intermediate 2 was added, the temperature was raised to 90°C, and a mixed solution of 0.89 mL of 1-chlorohexane and N,N-dimethylformamide was added dropwise for 2 min, and the reaction was continued at a constant temperature for 7 h. After the reaction, the flask was cooled, filtered, washed with water, dried, and recrystallized to obtain an anti-aging additive;
[0073] S4: After drying the polystyrene and the anti-aging additive, melt-blending them at 220° C. for 13 min, and hot-pressing to obtain the anti-aging layer material.
[0074] This embodiment discloses a method for preparing an aging-resistant flame-retardant energy storage charging cable, comprising the following steps:
[0075] Step 1: Twist 45 tinned soft copper wires into one strand, arrange and twist them according to one strand in the center and eight strands on the outer layer, and press them tightly to obtain a conductive core conductor. Wrap natural rubber around the outside of the conductive core conductor and combine them tightly to obtain a conductive core.
[0076] Step 2: Arrange the conductive wire cores with one in the center and six on the outer layer, wrap them with a winding lining layer, wrap a layer of armor layer on the outside of the winding lining layer, then wrap a layer of flame retardant layer material on the outside of the armor layer, and wrap a layer of aging-resistant layer material on the outside of the flame retardant layer. After tightly combining, an aging-resistant flame-retardant energy storage charging cable is obtained. Example 3
[0077] This embodiment discloses a method for preparing a flame retardant layer material, comprising the following steps:
[0078] Q1: 40.00g toluene, 20.00g polymethylhydrogensiloxane and 0.02g chloroplatinic acid were added to a three-necked flask equipped with a reflux condenser and a magnetic stirrer, wherein 5.5g chloroplatinic acid was dissolved with 1L isopropanol, heated to 80°C under a nitrogen atmosphere, and then 29g methyl methacrylate was slowly added dropwise for 1.5h, and then heated to react at 140°C for 32h. After the reaction, it was distilled under reduced pressure, washed with ethanol, and centrifuged to obtain product 1. Product 1 and a sodium hydroxide solution with a volume fraction of 10vt% were added to a flask equipped with a fractionation device, heated to 120°C for hydrolysis for 2h, methanol was fractionated to obtain a reaction solution, a dilute hydrochloric acid solution was added dropwise to the reaction solution to adjust the pH to 6, a precipitate was obtained, washed, and dried at 70°C for 10h to obtain carboxylated silicon;
[0079] Q2: 1.0 g of chitosan with a deacetylation degree of 95% was dissolved in an acetic acid solution to obtain a chitosan solution, and 10.0 g of ammonium polyphosphate with a degree of polymerization greater than 1000 was uniformly dispersed in deionized water, and then the chitosan solution was added dropwise, stirred for 5 min, and centrifuged at 4000 rpm for 8 min to obtain a precipitate, which was washed to obtain product II, and product II was uniformly dispersed in deionized water to obtain a suspension, and then 0.9 g of carboxylated silicon was dissolved in dilute ammonia water, and the pH was adjusted to 8 and then added to the suspension, stirred, washed, and centrifuged to obtain product III, and product III was vacuum dried at 60°C for 12 h to obtain a white powder;
[0080] Q3: After the polyethylene and white powder were vacuum dried, they were melt-blended at 170°C for 10 min at a rotation speed of 70 rpm, preheated at 2 MPa and 180°C for 5 min, then pressurized to 30 MPa, maintained at 180°C for 3 min, and then compressed at room temperature and 30 MPa for 3 min to obtain the flame retardant layer material.
[0081] This embodiment discloses a method for preparing an anti-aging layer material, comprising the following steps:
[0082] S1: 18.28 g of cyanuric chloride was dissolved in toluene, and 42.2 g of N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine was slowly added under an ice-water bath. After the reaction, an aqueous sodium hydroxide solution was added, and the mixture was heated at 70°C for 14 h. After the reaction, the mixture was extracted with water and ethyl acetate for 3 times, and the organic phases were separated and combined, dried, rotary evaporated, and vacuum dried to obtain intermediate 1;
[0083] S2: In an ice-water bath, add 1.55 g of intermediate 1, 10 mL of chlorobenzene and 0.41 g of anhydrous aluminum trichloride to a three-necked flask equipped with a mechanical stirrer and stir for 30 min. After stirring, add 0.31 g of hydroquinone to the three-necked flask, heat at 90°C for reaction for 5 h. After the reaction, slowly drop 2% by volume of dilute hydrochloric acid into the three-necked flask, distill at normal pressure, heat to 110°C, filter while hot, wash, and dry to obtain intermediate 2.
[0084] S3: 10 mL of N,N-dimethylformamide and 0.07 g of sodium hydroxide were added to a three-necked flask, heated at 50°C with stirring for 30 min, then 0.95 g of intermediate 2 was added, the temperature was raised to 90°C, and a mixed solution of 0.88 mL of 1-chlorohexane and N,N-dimethylformamide was added dropwise for 2 min, and the reaction was continued at a constant temperature for 7 h. After the reaction, the flask was cooled, filtered, washed with water, dried, and recrystallized to obtain an anti-aging additive;
[0085] S4: After drying the polystyrene and the anti-aging additive, melt-blending them at 220° C. for 13 min, and hot-pressing to obtain the anti-aging layer material.
[0086] The preparation method of the aging-resistant flame-retardant energy storage charging cable used in this embodiment is the same as that in Embodiment 2. Example 4
[0087] This embodiment discloses a method for preparing a flame retardant layer material, comprising the following steps:
[0088] Q1: 39.95g toluene, 21.10g polymethylhydrogensiloxane and 0.03g chloroplatinic acid were added to a three-necked flask equipped with a reflux condenser and a magnetic stirrer, wherein 5.5g chloroplatinic acid was dissolved with 1L isopropanol, heated to 80°C under a nitrogen atmosphere, and then 31g methyl methacrylate was slowly added dropwise for 1.5h, and then heated to react at 140°C for 32h. After the reaction, it was distilled under reduced pressure, washed with ethanol, and centrifuged to obtain product 1. Product 1 and a sodium hydroxide solution with a volume fraction of 10vt% were added to a flask equipped with a fractionation device, heated to 120°C for hydrolysis for 2h, methanol was fractionated to obtain a reaction solution, a dilute hydrochloric acid solution was added dropwise to the reaction solution to adjust the pH to 6, a precipitate was obtained, washed, and dried at 70°C for 10h to obtain carboxylated silicon;
[0089] Q2: 0.85 g of chitosan with a deacetylation degree of 95% was dissolved in an acetic acid solution to obtain a chitosan solution, and 10.2 g of ammonium polyphosphate with a polymerization degree greater than 1000 was uniformly dispersed in deionized water, and then the chitosan solution was added dropwise, stirred for 5 min, and centrifuged at 4000 rpm for 8 min to obtain a precipitate, which was washed to obtain product II, and product II was uniformly dispersed in deionized water to obtain a suspension, and then 1.2 g of carboxylated silicon was dissolved in dilute ammonia water, and the pH was adjusted to 8 and then added to the suspension, stirred, washed, and centrifuged to obtain product III, and product III was vacuum dried at 60°C for 12 h to obtain a white powder;
[0090] Q3: After the polyethylene and white powder were vacuum dried, they were melt-blended at 170°C for 10 min at a rotation speed of 70 rpm, preheated at 2 MPa and 180°C for 5 min, then pressurized to 30 MPa, maintained at 180°C for 3 min, and then compressed at room temperature and 30 MPa for 3 min to obtain the flame retardant layer material.
[0091] This embodiment discloses a method for preparing an anti-aging layer material, comprising the following steps:
[0092] S1: 18.78 g of cyanuric chloride was dissolved in toluene, and 42.4 g of N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine was slowly added under an ice-water bath. After the reaction, an aqueous sodium hydroxide solution was added, and the mixture was heated at 70°C for 14 h. After the reaction was completed, the mixture was extracted with water and ethyl acetate for 3 times, and the organic phases were separated and combined, dried, rotary evaporated, and vacuum dried to obtain intermediate 1;
[0093] S2: In an ice-water bath, add 1.7 g of intermediate 1, 14 mL of chlorobenzene and 0.49 g of anhydrous aluminum trichloride to a three-necked flask equipped with a mechanical stirrer and stir for 30 min. After stirring, add 0.39 g of hydroquinone to the three-necked flask and heat at 90°C for reaction for 5 h. After the reaction, slowly drop 2% by volume of dilute hydrochloric acid into the three-necked flask, distill at normal pressure, heat to 110°C, filter while hot, wash, and dry to obtain intermediate 2.
[0094] S3: 10 mL of N,N-dimethylformamide and 0.077 g of sodium hydroxide were added to a three-necked flask, heated at 50°C with stirring for 30 min, then 0.9 g of intermediate 2 was added, the temperature was raised to 90°C, and a mixed solution of 0.885 mL of 1-chlorohexane and N,N-dimethylformamide was added dropwise for 2 min, and the reaction was continued at a constant temperature for 7 h. After the reaction, the flask was cooled, filtered, washed with water, dried, and recrystallized to obtain an anti-aging additive;
[0095] S4: After drying the polystyrene and the anti-aging additive, melt-blending them at 220° C. for 13 min, and hot-pressing to obtain the anti-aging layer material.
[0096] The preparation method of the aging-resistant flame-retardant energy storage charging cable used in this embodiment is the same as that in Embodiment 2. Example 5
[0097] This embodiment discloses a method for preparing a flame retardant layer material, comprising the following steps:
[0098] Q1: 39.88g toluene, 20.08g polymethylhydrogensiloxane and 0.029g chloroplatinic acid were added to a three-necked flask equipped with a reflux condenser and a magnetic stirrer, wherein 5.5g chloroplatinic acid was dissolved in 1L isopropanol, heated to 80°C under a nitrogen atmosphere, and then 30.5g methyl methacrylate was slowly added dropwise for 1.5h, and then heated to react at 140°C for 32h. After the reaction, it was distilled under reduced pressure, washed with ethanol, and centrifuged to obtain product 1. Product 1 and a sodium hydroxide solution with a volume fraction of 10vt% were added to a flask equipped with a fractionation device, heated to 120°C for hydrolysis for 2h, methanol was fractionated to obtain a reaction solution, a dilute hydrochloric acid solution was added dropwise to the reaction solution to adjust the pH to 6, a precipitate was obtained, washed, and dried at 70°C for 10h to obtain carboxylated silicon;
[0099] Q2: 0.89 g of chitosan with a deacetylation degree of 95% was dissolved in an acetic acid solution to obtain a chitosan solution, and 10.05 g of ammonium polyphosphate with a degree of polymerization greater than 1000 was uniformly dispersed in deionized water, and then the chitosan solution was added dropwise, stirred for 5 min, and centrifuged at 4000 rpm for 8 min to obtain a precipitate, which was washed to obtain product II, and product II was uniformly dispersed in deionized water to obtain a suspension, and then 1.05 g of carboxylated silicon was dissolved in dilute ammonia water, and the pH was adjusted to 8 and then added to the suspension, stirred, washed, and centrifuged to obtain product III, and product III was vacuum dried at 60°C for 12 h to obtain a white powder;
[0100] Q3: After the polyethylene and white powder were vacuum dried, they were melt-blended at 170°C for 10 min at a rotation speed of 70 rpm, preheated at 2 MPa and 180°C for 5 min, then pressurized to 30 MPa, maintained at 180°C for 3 min, and then compressed at room temperature and 30 MPa for 3 min to obtain the flame retardant layer material.
[0101] This embodiment discloses a method for preparing an anti-aging layer material, comprising the following steps:
[0102] S1: 18.78 g of cyanuric chloride was dissolved in toluene, and 42.25 g of N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine was slowly added under an ice-water bath. After the reaction, an aqueous sodium hydroxide solution was added, and the mixture was heated at 70°C for 14 h. After the reaction, the mixture was extracted with water and ethyl acetate for 3 times, and the organic phases were separated and combined, dried, rotary evaporated, and vacuum dried to obtain intermediate 1;
[0103] S2: In an ice-water bath, 1.59 g of intermediate 1, 13 mL of chlorobenzene and 0.47 g of anhydrous aluminum trichloride were added to a three-necked flask equipped with a mechanical stirrer and stirred for 30 min. After the stirring, 0.33 g of hydroquinone was added to the three-necked flask, and the mixture was heated at 90°C for reaction for 5 h. After the reaction, 2% by volume dilute hydrochloric acid was slowly added dropwise to the three-necked flask, and distilled at normal pressure. The mixture was heated to 110°C, filtered while hot, washed, and dried to obtain intermediate 2.
[0104] S3: 10 mL of N,N-dimethylformamide and 0.073 g of sodium hydroxide were added to a three-necked flask, heated at 50°C with stirring for 30 min, then 1.1 g of intermediate 2 was added, the temperature was raised to 90°C, and a mixed solution of 0.895 mL of 1-chlorohexane and N,N-dimethylformamide was added dropwise for 2 min, and the reaction was continued at a constant temperature for 7 h. After the reaction, the flask was cooled, filtered, washed with water, dried, and recrystallized to obtain an anti-aging additive;
[0105] S4: After drying the polystyrene and the anti-aging additive, melt-blending them at 220° C. for 13 min, and hot-pressing to obtain the anti-aging layer material.
[0106] The preparation method of the aging-resistant flame-retardant energy storage charging cable used in this embodiment is the same as that in Embodiment 2.
[0107] Comparative Example 1
[0108] Compared with Example 2, in Comparative Example 1, carboxylated silicon is not added in the preparation of the flame retardant layer material, and other conditions remain unchanged.
[0109] Comparative Example 2
[0110] Comparative Example 2 Compared with Example 2, in Comparative Example 2, no N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine is added to the aging-resistant layer material, and other conditions remain unchanged.
[0111] Experimental example
[0112] The performance of the aging-resistant flame-retardant energy storage charging cables prepared in Examples 2-5 and Comparative Examples 1-2 was tested.
[0113] 1. Aging resistance test
[0114] The obtained samples were placed in a UV aging test chamber and exposed to UV light for 1000 hours according to GB / T 16422.3-2022. The tensile strength of the samples before and after UV irradiation was measured, and the tensile strength reduction rate was calculated. The results are shown in Table 1:
[0115]
[0116] It can be seen from the test results in Table 1 that the charging cables prepared in Examples 2-5 of the present invention have excellent aging resistance. It can be seen from the comparison between Comparative Example 2 and Examples 2-5 that the addition of N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine can effectively improve the aging resistance of the charging cable.
[0117] 2. Flame retardant performance test
[0118] The limiting oxygen index (LOI) of the obtained samples was measured using a Jiangning HC-2 oxygen index analyzer. According to the ASTM D3801 standard, the UL-94 vertical combustion test was carried out on a Jiangning CZF-Ⅲ vertical combustion test machine. The test results are shown in Table 2:
[0119]
[0120] It can be seen from the test results in Table 2 that the charging cables prepared in Examples 2-5 of the present invention have excellent flame retardant properties. It can be seen from the comparison between Comparative Example 1 and Examples 2-5 that the addition of carboxylated silicon can effectively improve the flame retardant properties of the charging cable.
[0121] 3. Mechanical properties test
[0122] The samples were placed in a tensile testing machine (Shandong Shijin Testing Equipment Co., Ltd.) for tensile strength testing. The test results are shown in Table 3:
[0123]
[0124] From the test results in Table 3, it can be seen that the charging cables prepared in Examples 2-5 of the present invention have excellent mechanical properties. From the comparison between Comparative Example 1 and Examples 2-5, it can be seen that the addition of carboxylated silicon can effectively improve the mechanical properties of the charging cable; from the comparison between Comparative Example 2 and Examples 2-5, it can be seen that the addition of N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine can effectively improve the mechanical properties of the charging cable.
[0125] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0126] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Aging-resistant flame-retardant energy storage charging cable, characterized in that: It includes a conductive core, a wrapped inner lining layer, an armor layer, a flame retardant layer and an aging-resistant layer arranged in sequence from the inside to the outside, wherein seven conductive cores are arranged, and one in the middle and six in the outer layer are closely combined, the conductive core includes an internal conductive core conductor and an external insulating layer, the seven conductive cores are twisted and connected to each other and the outer side thereof is wrapped with a wrapped inner lining layer, the outer side of the wrapped inner lining layer is wrapped with an armor layer, the outer side of the armor layer is wrapped with a flame retardant layer, and the outer side of the flame retardant layer is wrapped with an aging-resistant layer; The method for preparing the flame retardant layer material comprises the following steps: Q1: Toluene, polymethylhydrogensiloxane and chloroplatinic acid are added to a three-necked flask equipped with a reflux condenser and a magnetic stirrer, wherein chloroplatinic acid is dissolved with isopropanol, heated under a nitrogen atmosphere, and then methyl methacrylate is slowly added dropwise, followed by a heating reaction, and after the reaction is completed, vacuum distillation is performed, washed with ethanol, and centrifuged to obtain product 1, product 1 and sodium hydroxide solution are added to a flask equipped with a fractionation device, heated for hydrolysis, methanol is fractionated to obtain a reaction solution, a dilute hydrochloric acid solution is added dropwise to the reaction solution to adjust the pH, a precipitate is obtained, washed, and dried to obtain carboxylated silicon; Q2: Dissolve chitosan in acetic acid solution to obtain chitosan solution, and evenly disperse ammonium polyphosphate in deionized water, then add the chitosan solution dropwise, stir, centrifuge, obtain a precipitate, wash, and obtain product 2, evenly disperse product 2 in deionized water to obtain a suspension, then dissolve carboxylated silicon in dilute ammonia water, adjust the pH and add to the suspension, stir, wash, centrifuge, and obtain product 3, and vacuum dry product 3 to obtain a white powder; Q3: The polyethylene and white powder are vacuum dried, heated and melted, and then hot-pressed to obtain the flame retardant layer material; The method for preparing the anti-aging layer material comprises the following steps: S1: Dissolve cyanuric chloride in toluene, slowly add N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine in an ice-water bath, add sodium hydroxide aqueous solution after the reaction, heat to react, extract with water and ethyl acetate after the reaction, separate and combine the organic phases, dry, rotary evaporate, and vacuum dry to obtain intermediate 1; S2: In an ice-water bath, add intermediate 1, chlorobenzene and anhydrous aluminum chloride into a three-necked flask equipped with a mechanical stirrer and stir. After stirring, add hydroquinone into the three-necked flask and heat to react. After the reaction, slowly drop dilute hydrochloric acid into the three-necked flask, distill at normal pressure, heat, filter while hot, wash, and dry to obtain intermediate 2; S3: Add N,N-dimethylformamide and sodium hydroxide into a three-necked flask, heat and stir, then add intermediate 2, increase the temperature, dropwise add a mixed solution of 1-chlorohexane and N,N-dimethylformamide, continue the reaction at a constant temperature, cool, filter, wash, dry, and recrystallize to obtain an anti-aging additive; S4: drying the polystyrene and the anti-aging additive, melt-blending them, and hot-pressing them to obtain an anti-aging layer material.
2. The aging-resistant flame-retardant energy storage charging cable according to claim 1, characterized in that: The mass ratio of toluene, polymethylhydrogensiloxane, chloroplatinic acid and methyl methacrylate in Q1 is (39.8-40.1): (19.9-21.1): (0.002-0.003): (29-31), the dosage ratio of chloroplatinic acid to isopropanol is (4.5-6.1) g: 1L, heated to 80-90°C, the dropwise addition time is 1-2h, the heating reaction temperature is 140-150°C, the heating time is 30-34h, the volume fraction of the sodium hydroxide solution is 10vt%, the heating hydrolysis temperature is 100-120°C, the time is 2-3h, the pH is adjusted to 6, the drying temperature is 60-70°C, and the time is 10-12h.
3. The aging-resistant flame-retardant energy storage charging cable according to claim 1, characterized in that: The chitosan deacetylation degree of Q2 is 95%, the polymerization degree of ammonium polyphosphate is greater than 1000, the mass ratio of chitosan, ammonium polyphosphate and carboxylated silicon is (0.8-1.1):(10-10.2):(0.9-1.1), the stirring time after adding the chitosan solution is 3-5 minutes, the centrifugal speed after adding the chitosan solution is 3000-4000 rpm, the centrifugal time after adding the chitosan solution is 8-10 minutes, the pH is adjusted to 8, the vacuum drying temperature is 60-70°C, and the time is 10-12 hours.
4. The aging-resistant flame-retardant energy storage charging cable according to claim 1, characterized in that: The heating melting temperature in Q3 is 150-170°C, the blending time is 8-10min, the rotation speed is 60-80rpm, and the hot pressing process is: first preheating at 2MPa and 180°C for 5min, then pressurizing to 30MPa, maintaining at 180°C for 3min, and then compressing at room temperature and 30MPa for 3min.
5. The aging-resistant flame-retardant energy storage charging cable according to claim 1, characterized in that: The mass ratio of cyanuric chloride to N-n-butyl-2,2,6,6-tetramethyl-4-piperidinamine in S1 is (18-18.88):(42.12-42.5), the heating temperature is 70-80°C, the reaction time is 12-16h, and the number of extractions is 3-5 times.
6. The aging-resistant flame-retardant energy storage charging cable according to claim 1, characterized in that: In S2, the dosage ratio of intermediate 1, chlorobenzene, anhydrous aluminum chloride and hydroquinone is (1.5-1.7) g: (10-14) mL: (0.4-0.5) g: (0.3-0.4) g, the stirring time is 30-40 min, the heating temperature is 80-90° C., the heating time is 4-5 h, the volume fraction of dilute hydrochloric acid is 2vt%, and the heating temperature is 100-120° C.
7. The aging-resistant flame-retardant energy storage charging cable according to claim 1, characterized in that: In the S3, the dosage ratio of N,N-dimethylformamide, sodium hydroxide, intermediate 2 and the mixed solution is 10mL: (0.07-0.08)g: (0.9-1.1)g: (0.88-0.9)mL, the heating temperature is 40-50°C, the stirring time is 20-30min, the heating temperature is 80-90°C, the dropping time is 2-3min, and the continued reaction time is 6-7h; in the S4, the melting temperature is 220-240°C, and the blending time is 10-15min.
8. The method for preparing the aging-resistant flame-retardant energy storage charging cable according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Twist 40-50 tinned soft copper wires into one strand, arrange and twist them according to one strand in the center and eight strands on the outer layer, and press them tightly to obtain a conductive core conductor. Wrap natural rubber around the outside of the conductive core conductor and combine them tightly to obtain a conductive core. Step 2: Arrange the conductive wire cores with one in the center and six on the outer layer, wrap them with a winding lining layer, wrap a layer of armor layer on the outside of the winding lining layer, then wrap a layer of flame retardant layer material on the outside of the armor layer, and wrap a layer of aging-resistant layer material on the outside of the flame retardant layer. After tightly combining, an aging-resistant flame-retardant energy storage charging cable is obtained.
Citation Information
Patent Citations
Charging pile cable material and preparation method thereof
CN112980102A
Fire-resistant cable protective sleeve material, preparation method thereof and fire-resistant cable
CN116253945A
Photovoltaic cable with high ultraviolet aging resistance and preparation method thereof
CN117004110A